Optimisation and control of semi-active suspension using genetic algorithm for off-road full vehicle - BenLahcene, Zohir; Faris, Waleed Fekry; Ihsan, Sany Izan; Ridhuan Siradj , Fadly Jashi Darsivan (Inderscience Enterprises Ltd., 2014)
The main role of a suspension system of a vehicle is to prevent the road excitations from being transmitted to the passengers. In this study, we develop and obtain a strategy to optimise the main design parameters of a semi-active suspension for a two-axle full off-road vehicle. The objective is to minimise the maximum bouncing acceleration of the sprung mass. Owing to the importance of ride comfort for off-road vehicles, minimising the settling time and peak-to-peak of the vertical, pitch and roll acceleration would lead to better ride comfort. In solving this problem, the genetic algorithms have consistently found near-optimal solutions within specified parameters ranges for several independent runs.